THE EFFECTS OF INSTRUCTIONS ON THE EFFICIENCY OF EEG ALPHA POWER VOLUNTARY INCREASE TRAINING - O. Yu. Lazareva; O. M. Bazanova (Бюллетень сибирской медицины)
We studied how the efficiency of individual alpha power stimulating training depends on the use of instructions and the presence or absence of feedback. A new method of calculating the efficiency of a single training session was suggested.